Do defined contribution pensions correct for short-sighted savings decisions? Evidence from the UK - J. van de Ven (The Economic and Social Research Institute (ESRI), 2011)
Estimates for a structural model of savings and labour supply calculated on UK field data support the hypothesis of quasi-hyperbolic discounting. The estimated model indicates that a DC pension encourages increased saving and labour supply prior to pension age, and substantially reduced labour supply thereafter. These results are exaggerated when preferences are myopic. Welfare responses at the beginning of life to the DC pension improve with the extent of myopia, and with the return to the pension asset. Myopia represents an important factor in determining whether the DC pension results in a positive welfare response at plausible parameter values.
Keywords: D12; D81; H31; J26; 330; myopia; pension; saving; retirement; Altersvorsorge; Sparen; Flexible Altersgrenze; Großbritannien